GREEN SYNTHESIS OF ZINC OXIDE NANOPARTICLES WITH BIOLOGICAL ACTIVITY AND THEIR CHARACTERIZATION BY USING BANANA PEEL EXTRACT - Kalyani Pullapukuri 1, a), G. Sravan Kumar2, b), (Chelonian Research Foundation, 2023)
The anti-bacterial performance of ZnO nanoparticles, which have been effectively synthesised utilising banana feel extract, has been studied. To verify the synthesis, the structural, compositional, and morphological characteristics of the NPs were meticulously documented and examined. An UV-Vis absorption peak of 302 nm was noticed in the aqueous suspension of NPs, which essentially indicated their production. By using X-ray diffraction analysis, it was discovered that ZnO-NPs had a hexagonal wurtzite structure with an average particle size of 16.5nm. Some biomolecules and functional groups in the leaf extract were discovered using FTIR analysis to be in charge of the stability and encapsulation of ZnO-NPs. The material has the necessary constituent compositions, according to energy-dispersive X-ray analyses. At a grain size of about 15 nm, scanning electron microscopy revealed a flower-like morphology of ZnO nanoparticles. By using UV visible spectrophotometer to examine the NPs' optical characteristics, the band gap was determined to be 3.37 eV. The prepared ZnO-NPs have demonstrated antibacterial activity against gram negative bacteria V. cholerae, (MTCC-3906), S. flexneri (ATCC-12022), Enterobacter aerogenes (MTCC-241) and gram-positive bacteria Staphylococcus aureus (MTCC-3160), C. glutamicum (MTCC-2745), Clostridium perfringens (ATCC 13124). The maximum zone of inhibition 24.82±0.75mm (Fig.) against C. perfringens at the concentration of 200µg/mL followed by 21.86±0.35mm against S. flexneri and 20.46±0.50mm against V. chloreae at the concentration of 200µg/mL. It is clear from the creation of an inhibitory zone that membrane disruption is a necessary component of nanoparticles' biocidal effect. It is believed that ZnO's antibacterial ability is primarily caused by the generation of hydrogen peroxide on its surface. Key words: Banana peel extract, ZnO-NPs, Microorganisms, Antibacterial activity